Identification of Misconceptions with a Three-Tier Diagnostic Test on Elementary School Students' Force Topic - Anisa Wahyu Kusumaningtyas; Dilla Putri Meydawati; Nur Hanifatun Nadhif; M Anas Thohir; Lilik Bintartik (Postgraduate, University of Mataram, 2025)
Misconceptions must be addressed immediately because they can cause failure to achieve learning objectives. The purpose of this study was to identify misconceptions, determine the level of misconception categories in the concept of force, such as friction, spring force, and muscle force, and determine the science learning process in the material of force. This study has a uniqueness in the form of subjects used, namely schools participating in the Kampus Mengajar 7 program, where the literacy and numeracy conditions of students are relatively low. This study uses a qualitative approach, with research subjects being students and teachers of grade IV at one of the elementary schools in Blitar City. The data collected include the results of the Three-Tier Diagnostic test to identify misconceptions, interviews with teachers, and documentation. Data analysis methods consist of data reduction, data presentation, and drawing conclusions. The results of the study showed that there were misconceptions in the material of force in science learning, especially in friction, spring force, and muscle force. Of the three concepts of force, there are still misconceptions in the material of force based on its type, such as spring force and friction having a high category and muscle force with a low category. These findings highlight the need for more hands-on experimentation and contextualized instruction in elementary science education to reduce misconceptions. Meanwhile, in the science learning process, teachers use a direct instruction model with a few experiments.